PENGARUH PROGRAM SERTIFIKASI TANAH TERHADAP AKSES PERMODALAN BAGI USAHA MIKRO DAN KECIL STUDI KASUS PROGRAM SERTIFIKASI TAHUN 2008 DI KABUPATEN KULON PROGO - Istikomah, Istikomah (Jurnal Kawistara, 2013)
This paper discusses influence of land certification program on Micro and Small Enterprises (MSEs) to access capital through the identification of factors that influence the decision of micro and small entrepreneurs (MSEs) in the use of Certificate of Land Ownership (SHM) as collateral and identification of the influence of certificate program to increase total loans granted to MSEs as the land owner. The identification of the factors that influence the decision of MSEs in the use of SHM as loan collateral (Y1), use binary logit regression analysis with independent variable including credit application purposes (X1), the suitability of the number of credits earned by the required amount (X2), the preception of lending procedures financial institutions (X3), perceptions of ability to repay the loan (X4), the age of the respondent (X5), sex (X6), the education level of respondents (X7), MSEs participation in MSE land certificate program (X8) and the amount of labor (X9). Meanwhile, the identification of the factors that affect the increase in lending financial in the factors that affect the increase in lending financial institution (Y2) uses multiple linear regression analysis with the independent variables include omzet (X1), the use of certificates as collateral (X2), MSEs perception of the analysis applied to financial institutions (X3), the age of respondents (X4), sex (X5), educational level (X6), and participation in the program MSEs land certificate MSE (X7).